Clptm1, a new target in suppressing epileptic seizure by regulating GABAAR‐mediated inhibitory synaptic transmission in a PTZ‐induced epilepsy model. Issue 1 (15th December 2022) - Zhang, Xiao‐Lin; Zhou, Jin‐Yu; Zhang, Peng; Lin, Lan; Mei, Rong; Zhang, Feng‐Li; Chen, Yang‐Mei; Li, Rong
Abstract: Disruption of gamma‐amino butyric acid type A receptors (GABAA Rs) synaptic clustering and a decrease in the number of GABAA Rs in the plasma membrane are thought to contribute to alteration of the balance between excitatory and inhibitory neurotransmission, which promotes seizure induction and propagation. The multipass transmembrane protein cleft lip and palate transmembrane protein 1 (Clptm1) controls the forward trafficking of GABAA R, thus decaying miniature inhibitory postsynaptic current (mIPSC) of inhibitory synapses. In this study, using a pentylenetetrazol (PTZ)‐induced epilepsy rat model, we found that Clptm1 regulates epileptic seizures by modulating GABAA R‐mediated inhibitory synaptic transmission. First, we showed that Clptm1 expression was elevated in the PTZ‐induced epileptic rats. Subsequently, we found that downregulation of Clptm1 expression protected against PTZ‐induced seizures, which was attributed to an increase in the number of GABAA Rγ2s in the plasma membrane and the amplitude of mIPSC. Taken together, our findings identify a new anti‐seizure target that provides a theoretical basis for the development of novel strategies for the prevention and treatment of epilepsy.